Student's Grammatical Ability With Dictogloss Method - Gitit Indra Putra Wacana (Sintuwu Maroso Journal of English Teaching, 2022)
This research is a scientific step that aims to improve students' English competence through an interactive English grammar learning process, namely the Dictogloss Technique. The dictogloss technique is a learning activity using dictation techniques, by listening to oral discourse, identifying key words and working together in small groups to reconstruct the dictated discourse. The method used in this research is quasi-experimental with the division of experimental class and control class. The results showed that the Dictogloss method has no significant effect on increasing students grammatical abilities.